Bargaining and social dialogue at the public sector (BARSOP) country study: Czechia - Martiskova, Monika (Bratislava, 2018)
"In this report, we investigate the impact of industrial relations and social dialogue on the quality of employment, and subsequently, on the quality of services provided in the public sector in Czechia since 2000, with a special emphasis given to the changes and developments in the postcrisis period. Industrial relations in the Czech public sector are marked by fragmentation and the absence of collective bargaining in the majority of public sector domains. Despite the high level of decentralization, wage setting and provisions for working conditions, have remained centralized with the unilateral decision of the government. In the analysis we applied a multidisciplinary and multi-level governance perspective using available data, documents and semi-structured interviews to support the evidence. The analysis focused on the three subsectors of the public sector, namely healthcare (with a focus on hospitals), primary education and municipalities (with a focus on pre-primary education). This approach allowed mapping sectoral differences within the public sector in the social dialogue outcomes. Our results suggest that the impact of the crisis on public sector employment remained limited. The Czech government implemented simple budget cuts that were set in motion only at the central government level. The limited impact of the crisis in the education and healthcare sector is linked to the mobilization and protest activities of the trade unions in this period. In both sectors, low wages were used as the main argument to prevent budget cuts. As a result, the crisis has strengthened the position of trade unions and has exercised their mobilization potential, but was not sufficient to institutionalize collective bargaining in the public sector, as since the crisis period, only one sector’s collective agreement has been concluded.."